Associations of macular thickness in spectral-domain OCT with ocular and systemic cardiovascular parameters: the MIPH Eye and Health Study - Schuster, Alexander K.; Fischer, Joachim E.; Voßmerbäumer, Urs (Graefe's archive for clinical and experimental ophthalmology, 2015)
Purpose: Beyond in-vivo histological analysis of retinal tissue, optical coherence tomography (OCT) allows quantitative image analysis. This study evaluates associations of macular retinal thickness measured with spectral-domain OCT (SD-OCT) and ocular and systemic cardiovascular parameters in adult subjects. Methods: An epidemiological cross-sectional study was performed in the staff of a European high-tech company. Examination of known cardiovascular risk factors including biochemical blood analysis was performed, and ocular parameters such as refraction, tonometry, SD-OCT imaging of the macula and cornea, and fundus photography were evaluated. Retinal thickness measurements were evaluated according to the ETDRS grid. Associations of macular retinal thickness and systemic cardiovascular and ocular parameters were calculated by multivariate analysis using SPSS software. Results: Four hundred and twenty-four probands were included. Macular thickness measurement were significantly associated with gender and refraction. Female persons had thinner retinal thickness in all zones. Macular thickness decreased with increasing myopia in all perifoveal measurements. Outer perifoveal measurements were associated with keratometry; a flatter corneal radius was linked to a thinner retina. Tonometry and systemic cardiovascular risk factors were not associated with macular retinal thickness in multivariate analysis (p > 0.05). Conclusions: Macular retinal thickness is associated with refraction and gender; cardiovascular risk factors or tonometry do not influence macular retinal thickness measurements. Keratometry might influence outer zone measurements. Our findings provide a dataset for quantitative evaluation of SD-OCT, and evaluate influencing factors.
Online veröffentlicht: 26. September 2014
Gesehen am 06.09.2017